42nd JACT Latin Summer School – 2022 Director's Report. Issue 47 (2023) - Stephenson, David
Abstract: This is a review of the activities and successes of the 42nd residential JACT Latin Summer School, run in July 2022. Specifically, it covers our typical teaching arrangement, lectures, trips and events and acknowledges the generosity of our sponsors.